Perioperative transfusion for pancreaticoduodenectomy and its impact on prognosis in resected pancreatic ductal adenocarcinoma - Clark, E. (2007)
Background and aims: Pancreaticoduodenectomy (PD) is a major operative intervention performed most commonly for malignancy in the head of pancreas. The aim of this study was to evaluate the utilization of blood transfusion for PD and to determine whether this had prognostic significance in a subset of patients with pancreatic ductal adenocarcinoma (PDAC). Material and methods: Data on blood transfusion requirement were retrospectively collected for patients undergoing PD from 1998 to 2005. Standard prognostic factors and survival data were also collected in patients with PDAC. Results: One-hundred-and-seventy patients underwent PD. Seventy-six patients (45%) received transfusion. The median (interquartile range) number of units of red cell concentrate (RCC) transfused perioperatively (intraoperatively and within 24 h of surgery) was 1.5 (0.5–2.5). The median preoperative haemoglobin (Hb) was 126 g/dl. The median number of units of RCC transfused perioperatively in patients with Hb <126 g/dl was 2 (1–3); for those with Hb ≥ 126 g/dl the median was 0 (0–1); p=0.003. Forty-nine patients who were resected for PDAC were subjected to survival analysis. Univariate and multivariate analyses showed that only posterior resection margin invasion was associated with an adverse outcome (margin positive 198 [143–470] days vs margin negative 398 [303–859] days; p=0.02). Perioperative RCC transfusion requirement was not a significant predictor of survival (transfusion 408 [214–769] days vs no transfusion 331 [217–391] days; p=0.18). Furthermore, RCC transfusion within 30 days of operation was not a significant predictor of poor survival (transfusion 331 [201–459] days vs no transfusion 317 [196–769] days; p=0.43). Conclusions: PD can be performed with a moderately low requirement for RCC transfusion; however, low preoperative haemoglobin is a predictor for the requirement of RCC transfusion. Administration of RCC transfusion does not appear to be a significant adverse prognostic factor in patients with resected PDAC.